The moral target aiming at right conduct in war and other conflicts - Kamm, F. M. (Frances Myrna) (Oxford : Oxford University Press, 2013)
This title comprises essays that discuss aspects of war and other conflicts in the light of nonconsequentialist ethical theory. The topics include the relation between conditions that justify starting war and those that justify stopping it, the treatment of combatants and noncombatants in war, and much more.
Series from CIP print record.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: War -- Moral and ethical aspects; Just war doctrine; Military ethics